Corporate social strategy ; stakeholder engagement and competitive advantage - Husted, Bryan W. 1957- (Cambridge University Press, 2011)
"Can good-will be good business? Firms are increasingly called upon to address matters such as poverty and human rights violations. The demand for corporate social responsibility (CSR) is directed mainly at top management in multinational corporations who are reminded that, in addition to helping to make the world a better place, their commitment to social action will be rewarded by lasting customer loyalty and profits. But is it true that firms that engage in social action will be rewarded with a good name, competitive advantage, superior profits and corporate sustainability? What if it is true for some firms and not for others? This book addresses these and other questions by explaining the how and why of creating value and competitive advantage through corporate social action. It shows how and when firms can develop successful corporate social strategies that establish strong commitments to shareholders, employees and other stakeholders"--Provided by publisher.